Achieving the cost-effective energy transformation of Europe’s buildings - Filippidou, Faidra; Jiménez-Navarro, Juan-Pablo (My University, 2019)
This report aims to answer the following question: Which are the most cost-effective ways to decarbonise the existing EU building sector through energy renovations? Replying this, we provide a method and a dataset to investigate the cost-optimal level of energy efficiency measures in combination with low carbon heating and cooling solutions. To showcase the application of the method, two EU Member States (Germany and Greece) are examined and targeted renovation solutions are discussed as examples.
Achieving the cost-effective energy transformation of Europe’s buildings. Combination of insulation and heating and cooling technologies renovationsMethods and data
Política de acceso abierto de la editorial: https://commission.europa.eu/legal-notice_en#copyright-notice
Keywords: Aire acondicionado; Decarbonisation of buildings; EU building stock; Building renovation